2019
DOI: 10.3168/jds.2018-15022
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Blood metabolites, body reserves, and feed efficiency of high-producing dairy cows that varied in ruminal pH when fed a high-concentrate diet

Abstract: Recent studies report considerable variation in ruminal pH for lactating dairy cows even when fed the same diet. We hypothesized that blood metabolites would be indicators of low ruminal pH, and hence could be used as predictors to help manage this variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…TABELEÃO et al (2008) identified that the inclusion of yeast-based additives in a balanced diet promotes changes in liver function, which were evidenced by the increased activity of GGT enzyme during the adaptation period, which did not occur in the present study, but demonstrates that these products may be related to the increase in the activity of hepatocytes. NASROLLAHI et al (2019) and XU et al (2016) reported an increase in the serum activity of AST in cows with lower ruminal pH, indicating that there is a relationship between the drop in pH and the liver efficiency of these animals, partially explaining the results reported in the present study. Still, NASROLLAHI et al (2019) suggested that AST serum activity may be a possible indicator of susceptibility to low ruminal pH values.…”
Section: Discussionsupporting
confidence: 76%
“…TABELEÃO et al (2008) identified that the inclusion of yeast-based additives in a balanced diet promotes changes in liver function, which were evidenced by the increased activity of GGT enzyme during the adaptation period, which did not occur in the present study, but demonstrates that these products may be related to the increase in the activity of hepatocytes. NASROLLAHI et al (2019) and XU et al (2016) reported an increase in the serum activity of AST in cows with lower ruminal pH, indicating that there is a relationship between the drop in pH and the liver efficiency of these animals, partially explaining the results reported in the present study. Still, NASROLLAHI et al (2019) suggested that AST serum activity may be a possible indicator of susceptibility to low ruminal pH values.…”
Section: Discussionsupporting
confidence: 76%
“…In the Weaning group, AST activity and ALP concentration increased significantly at 3 weeks after weaning, and calves in the Starter group showed higher serum AST and GGT activities and ALP concentration, which are indicators of liver function in ruminants [3, 17, 24]. Cattle with hepatic toxicity induced by poultry litter consumption showed higher serum levels of GGT and ALP than healthy cattle [24], and the concentration of ALP increased in goats fed a high-grain diet [3].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Nasrollahi et al . [17] suggested that blood metabolite concentrations may help to predict susceptibility of cows to SARA, and serum AST activity was negatively correlated with ruminal pH in dairy cows. In the present study, GGT activity was negatively correlated with 24 hr mean ruminal pH, and was lower in the Starter group during weaning transition, although we could not find any correlation between serum AST activity and ruminal pH.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies the increasing valerate, propionate, butyrate and isovalerate have been associated with greater feed efficiency (Guan et al, 2008;Kruger Ben Shabat et al, 2016). Valerate is precursor of odd chain fatty acids (OCFA), incorporated into ruminal bacteria responsible for increased ruminal propionate (Nasrollahi et al, 2019). In addition, recent research has indicated that an increase in valerate concentration in ruminal fluid, was negatively correlated with milk fat content (Nasrollahi et al, 2019); The autors related valerate with a low ruminal pH (< 5.80) and with an increase in aspartate amino-transferase (AST) activity, which may signalize liver disorders and cause a decrease in milk fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Valerate is precursor of odd chain fatty acids (OCFA), incorporated into ruminal bacteria responsible for increased ruminal propionate (Nasrollahi et al, 2019). In addition, recent research has indicated that an increase in valerate concentration in ruminal fluid, was negatively correlated with milk fat content (Nasrollahi et al, 2019); The autors related valerate with a low ruminal pH (< 5.80) and with an increase in aspartate amino-transferase (AST) activity, which may signalize liver disorders and cause a decrease in milk fat content. We observed a decrease tendency on milk fat content with CSPOL-400, but we did not observe low pH values.…”
Section: Discussionmentioning
confidence: 99%